Senjata Kurambik Dalam Fotografi Produk - Oktavian, Riki (Matalensa: Journal of Photography and Media, 2022)
ABSTRACT This thesis is entitled "Kurambik Weapons in product photography”. The purpose of this thesis is to create a product work using Kurambik Weapons as the main object to help promotion from Kurambik Weapons products. The data collection methods used are: observation, literature study, and interviews. From the observation process that has been carried out by the planter in sulayan jorong precisely at the place of manufacture site typical minang kurambik. Minang's signature Kurambik weapon comes with a defense typical miangkabau kurambik with characteristics carving Of Rumah Gadang and the manufacture is stil using hands or manually. The technique used when photographing silver ring crafts is low key. Low key, so that the resulting photo looks alive because the background tends to be black with the main object being more dominant in contrast from the surroundings so that the weapons Kurambik photo looks elegant.  Product photography is intended for advertising of a product, poster, or other with an interesting point of view of potential consumers. KataKunci: Kurambik, Product photography,PitalahABSTRAKKarya ini berjudul“Senjata Kurambik dalam fotografi produk. Skripsi karya bertujuan menciptakan karya fotografi produk dengan menggunakan Senjata Kurambik khas Minang sebagai objek utama yang akan digunakan sebagai media promosi. Metode pengumpulan data yang digunakan yaitu: observasi, studi pustaka, dan wawancara. Dari Proses pengamatan yang telah dilakukan pengkarya di jorong Sulayan tepatnya di tempat lokasi pembuatan kurambik khas Minang. Senjata  Kurambik khas Minang hadir dengan pempertahankan Kurambik khas Minangkabau dengan ciri khas ukiran Rumah gadang serta pembuatan yang dilakukan masih menggunakan tangan atau manual. Teknik yang digunakan saat memotret senjata kurambik adalah low key  agar foto yang dihasilkan terlihat elegan karena background cenderung hitam dengan objek utama lebih dominan kontras dari sekitarnya agar foto senjata kurambik terlihat elegan.Fotografi produk diperuntukan iklan dari sebuah produk,  poster, atau yang lainnya dengan sudut pandang yang menarik calon konsumen.KataKunci:Kurambik,Fotografi produk,Pitalah